Pengaruh Leverage, Kepemilikan Institusional, dan Kepemilikan Manajerial terhadap Penghindaran Pajak - Galuh Adella Lokahita; Sevty Wahiddirani Saputri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to analyze empirical evidence on how leverage, institutional ownership, and managerial ownership impact tax avoidance in non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The research uses a quantitative associative method, relying on secondary data from IDX’s website and annual reports of the companies. Sampling was conducted using purposive sampling based on specific criteria relevant to the study, resulting in a sample of 9 companies with 113 observations. Hypothesis testing was performed using Eviews 10 for data analysis and Excel 9 for data management. The findings reveal that, collectively, leverage, institutional ownership, and managerial ownership have a significant impact on tax avoidance. However, when examined individually, only leverage shows a significant effect on tax avoidance. Institutional and managerial ownership do not significantly influence tax avoidance. This lack of impact might be due to differences in the motivations and capabilities of institutional and managerial shareholders in implementing tax strategies. The study underscores the critical role of leverage in managing tax strategies. High leverage can increase financial pressure on a company, potentially driving it to engage in tax avoidance to preserve profitability. Conversely, the influence of institutional and managerial ownership on tax avoidance is less clear, suggesting that these ownership structures may not significantly alter tax avoidance behaviors. This research contributes to the existing literature on tax avoidance by highlighting the importance of leverage and provides valuable insights for companies aiming to develop more effective financial and ownership policies for efficient tax management.